2008
DOI: 10.1016/j.jhep.2007.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog is an autocrine viability factor for myofibroblastic hepatic stellate cells

Abstract: Background/Aims-Factors released during liver injury, such as platelet derived growth factor-BB (PDGF) promote accumulation of myofibroblastic hepatic stellate cells (MFB) that drive the pathogenesis of cirrhosis. The Hedgehog (Hh) pathway regulates remodeling of other injured tissues. This study evaluates the hypothesis that autocrine production of Sonic hedgehog (Shh) promotes MFB growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
203
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(218 citation statements)
references
References 66 publications
13
203
0
1
Order By: Relevance
“…Shh shown to be involved in activation of HSCs (6,8,42). In day 7 culture-activated HSCs, Dlk1 mRNA expression is suppressed by inhibition of canonical Wnt signaling with the Wnt co-receptor antagonist Dickkopf-1 (DKK1), necdin shRNA, and the Shh inhibitor cyclopamine (Fig.…”
Section: Dlk1 Under Control Of Cross-interactions With Other Morphogementioning
confidence: 98%
“…Shh shown to be involved in activation of HSCs (6,8,42). In day 7 culture-activated HSCs, Dlk1 mRNA expression is suppressed by inhibition of canonical Wnt signaling with the Wnt co-receptor antagonist Dickkopf-1 (DKK1), necdin shRNA, and the Shh inhibitor cyclopamine (Fig.…”
Section: Dlk1 Under Control Of Cross-interactions With Other Morphogementioning
confidence: 98%
“…In vitro , it has been well documented that recombinant Shh protein induces an activated phenotype of cultured lung fibroblasts and hepatic stellate cells, as manifested by an augmented cell proliferation, migration, excessive ECM production (Hu et al, 2015; Yang et al, 2008). Shh signaling is upregulated in animal models and patients with idiopathic pulmonary fibrosis (IPF), other interstitial lung diseases and nonalcoholic fatty liver disease (NAFLD), with nuclear accumulation of Gli1, Gli2 in the fibrotic areas and an increased expression of the Shh downstream target genes.…”
Section: Shh Signaling and The Fibrotic Disease Of Other Organsmentioning
confidence: 99%
“…27 Recent data demonstrated that Shh contributes to PDGF-BBstimulated fibroblast migration. 20 Because PDGF-BB is one of the main chemotactic factors for SMCs, we hypothesized that Hh proteins could work in combination with PDGF-BB to promote SMC migration. As shown in Figure 1A, Hh blocking antibody 5E1 decreased PDGF-BB-induced migration of commercial rat aortic primarycultured SMCs.…”
Section: Hh Proteins and Hh Pathway Activation Are Required For Pdgf-mentioning
confidence: 99%
“…Because Shh was previously shown to promote SMC proliferation in vitro [16][17][18] and to drive the proliferative effect of PDGF-BB, 20 we checked the role of the Hh pathway in NG2…”
Section: Early Recruitment Of Ng2mentioning
confidence: 99%
See 1 more Smart Citation